Analisis Pemberian Dispensasi Nikah di Pengadilan Agama Krasaan Perspektif Hukum Positif - Alfan Patoni; Imam Bukhori; Abd Hannan (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the practice of granting marriage dispensation at the Kraksaan Religious Court from the perspective of positive law in Indonesia. Marriage dispensation is the court's authority to grant marriage permits for couples who have not reached the minimum age limit as stipulated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. The research method used is qualitative with a juridical-sociological approach. Data were obtained through interviews with judges and studies of marriage dispensation decisions at the Kraksaan Religious Court during the enactment of Law Number 16. The results of the study indicate that the granting of marriage dispensation at the Kraksaan Religious Court is still dominated by reasons of pregnancy outside marriage and family pressure, although normatively it must consider aspects of the welfare and protection of children. In practice, judges tend to use social and psychological considerations in deciding cases, although sometimes they do not fully refer to the spirit of child protection in positive law. These findings indicate a tension between social reality and applicable legal norms, so that synergy is needed between regulations, public education, and child protection policies.